Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.0021-8790.2004.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Stage‐structured harvesting and its effects: an empirical investigation using soil mites

Abstract: Summary 1.Population dynamics results from an interplay between the environmental state and population density. With many organisms there is structure to the life history, and this structure has important consequences for the population's density dependence and its interaction with environmental noise, and therefore its population dynamics. Perturbing population structure, such as through harvesting, may therefore affect the way that the populations respond to stochastic environmental variation. 2. We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 49 publications
3
97
0
Order By: Relevance
“…Note that adult biomass decreases with harvesting (no overcompensation) in panel (d) and increases with harvesting (overcompensation) in panel (e). Data were generously provided by T. Cameron and J. Ohlberger (Cameron andBenton 2004, Ohlberger et al 2011). increases in mass-specific rates do not compensate for the decreases in juvenile and adult biomasses. Overall, the monotonic decrease in biomass with increased mortality corresponds to well-known patterns observed in unstructured consumer-resource models.…”
Section: Overcompensation In Biomass As a Results Of Ontogenetic Asymmmentioning
confidence: 99%
“…Note that adult biomass decreases with harvesting (no overcompensation) in panel (d) and increases with harvesting (overcompensation) in panel (e). Data were generously provided by T. Cameron and J. Ohlberger (Cameron andBenton 2004, Ohlberger et al 2011). increases in mass-specific rates do not compensate for the decreases in juvenile and adult biomasses. Overall, the monotonic decrease in biomass with increased mortality corresponds to well-known patterns observed in unstructured consumer-resource models.…”
Section: Overcompensation In Biomass As a Results Of Ontogenetic Asymmmentioning
confidence: 99%
“…We reviewed the literature for three types of experimental evidence that can reveal the likely occurrence of emergent facilitation (Table 1). First, biomass increases in a particular population stage, in response to increased mortality imposed on another stage, have been shown to occur in laboratory populations of blowflies (21), soil mites (22), and fish (A. Schröder, L.P., and A.M.D.R., unpublished data). Second, increases in stage-specific prey density, because of variation in predation pressure, have been shown to occur in cladocerans in both laboratory (24) and field enclosures (25).…”
Section: Discussionmentioning
confidence: 99%
“…Such indirect effects of mortality may result in increased stage-specific biomass production thereby compensating for the removal of individuals from the population (Werner andGilliam 1984, De Roos et al 2007). Experimental studies on laboratory populations have shown that stage-specific biomass remains unchanged or increases if not all individuals are subjected to increased mortality rates, for instance in water fleas (Slobodkin and Richman 1956), blowflies (Nicholson 1957), soil mites (Cameron and Benton 2004), and fish (Schro¨der et al 2009). Differences in mortality rates between size classes or life stages of natural populations are commonly observed in nature and may arise from size-specific predation (Brooks andDodson 1965, Werner andGilliam 1984), harvesting by humans (Law 2000, Fenberg andRoy 2008), or parasite infections (Ohlberger et al 2011b).…”
Section: Introductionmentioning
confidence: 99%